WOMEN'S IMAGE IN THE COLLECTION OF SHORT STORY CARI AKU DI CANTI BY WA ODE WULAN RATNA - Darminton Mondolalo (Journal of Indonesian Language Education and Literary, 2016)
In the history Indonesian literary, the short story is a literary genre and younger than the poetry and novels. Short Story is one of the terms in works of fiction whose presence adds a new kind of literary works in the world of Indonesian literary. This study raises issues of women’s image in the collection of short story Cari Aku di Canti-Find Me at Canti by Wa Ode Wulan Ratna. The purpose of this study was to describe the data and information contained in this collection of short story Cari Aku di Canti-Find Me at Canti by Wa Ode Wulan Ratna. Based on the results of the discussion and data analysis can be concluded that the image of women can be divided into several parts; (A) the image of women as individuals, it is the image of women's physical and image of women psychologically, (b) the image of women as members of the family, which is the image of women as housewives and the image of women as a child, and (c) the image of women as members society, namely interpersonal relationships and personal relationships with the community. Both stories is the theme of traditional matchmaking, matchmake the men and women committed by the parents of both parties. However, the two main characters of short story resisting traditional matchmaking system. Resistance can be seen from the actions of Harima protagonist in the short story and the Malino Bula Johra main character in the short story La Runduma